CHARACTERIZATION OF ANTIVIRAL PROPERTIES OF TRAPPIN-2 AND ELAFIN AGAINST HIV-1 AND HSV-2 IN THE FEMALE GENITAL MUCOSA - Drannik, Anna (My University, 2012)
Sexually transmitted infections (STIs), especially HIV/AIDS and HSV-2, continue to be a devastating burden on societies around the world. The close link between HSV-2 and HIV-1, the role of inflammation in driving these infections, and the limited success and availability of prophylactic and therapeutic measures underscore the need for continued search of alternative means of protection. Characterization of endogenous antimicrobials, especially those local to the female genital tract and actively regulating inflammatory and antiviral responses, could be beneficial for microbicidal trials. Although regulators of mucosal immunity, such as serine antiproteases, trappin-2 and elafin (Tr/E), have been associated with resistance to HIV-1, their antiviral activity remains poorly understood. Thus, the research presented in this thesis centers on characterization of antiviral properties of Tr and E individually and their potential mechanisms in defense against HSV-2 and HIV-1 in the female genital mucosa. Chapter 2 examines Tr/E contribution to antiviral host defense responses elicited by a synthetic mimic of viral dsRNA, polyI:C. Chapter 3 documents the presence and characteristics, including potential mechanisms, of antiviral activity of Tr/E against in vitro and in vivo HSV-2 infection. Chapters 4 and 5 determine the contribution of Tr/E to the natural anti-HIV-1 protection of CVL and structural characteristics, mode(s) of action, and cellular distribution/localization of antiviral Tr/E proteins. Therein, we present novel properties of each Tr/E by demonstrating their inhibitory and multiple effects against both HSV-2 and HIV-1. These effects appear to be mediated either through virus or cells and be associated with altered viral attachment/entry, transcytosis and infection, innate viral recognition, modulated inflammation and increased antiviral protection of cells. Reported antiviral activity of Tr/E was also contextual and exerted, at least in HEC-1A cells, via autocrine/paracrine mode and depended on elafin’s nuclear localization and its unmodified N-terminus. Tr/E may represent viable candidates for further studies in the field of STIs.
Keywords: trappin-2; elafin; sexually-transmitted infections; HIV-1; HSV-2; polyI:C; inflammation; innate; antiviral; Medical Immunology; Medical Microbiology; Reproductive and Urinary Physiology; Viruses; Medical Immunology